Elevated CO2 and temperature under future climate change increase severity of rice sheath blight - Shen, Min; Cai, Chuang; Song, Lian; Qiu, Jiangbo; Ma, Chuanqi; Wang, Dongming; Gu, Xinyue; Yang, Xiong; Wei, Wei; Tao, Ye; Zhang, Jishuang; Liu, Gang; et al. (Frontiers in Plant Science, 2023)
Sheath blight (ShB), caused by Rhizoctonia solani, is one of the major threats to rice (Oryza sativa L.) production. However, it is not clear how the risk of rice ShB will respond to elevated CO2 and temperature under future climate change. Thus, field experiments of inoculated R. solani were conducted under combinations of two CO2 levels (ambient and enriched up to 590 μmol mol-1) and two temperature levels (ambient and increased by 2.0 °C) in temperature by free-air CO2 enrichment (T-FACE) system for two cultivars (a susceptible cultivar, Lemont and a resistant cultivar, YSBR1). For inoculation of plants with R. solani, the vertical length of ShB lesions for cv. Lemont was significantly longer than that for cv. YSBR1 under four CO2 and temperature treatments. The vertical length of ShB lesions was significantly increased by elevated temperature, but not by elevated CO2, for both cultivars. The vertical length of ShB lesions under the combination of elevated CO2 and elevated temperature was increased by 21–38 % for cv. Lemont and by -1–6 % for cv. YSBR1. A significant increase in MDA level was found to a significant increase in the vertical length of ShB lesions under the combination of elevated CO2 and elevated temperature. Elevated CO2 could not compensate for the negative effect of elevated temperature on yield of both cultivars under future climate change. Rice yield and biomass were further decreased by 2.0–2.5 % and 2.9–4.2 % by an increase in the severity of ShB under the combination of elevated CO2 and elevated temperature. Reasonable agronomic management practices are required to improve both resistance to ShB disease and grain yield for rice under future climate change.